ANALISIS DETERMINAN NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR BASIC MATERIAL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2020 - Naufal Aria Weenas Pratama (2022)
This research is a quantitative research that has the aim of knowing the effect of Capital Structure proxied by Debt Equity Ratio (DER), Liquidity proxied by current ratio (CR), and profitability as proxied by Return on equity (ROE) on Firm Value. proxied Price to Book Value (PBV). This study examines the population of the basic material sector listed on the Indonesia Stock Exchange (IDX) in 2017-2020. The technique used in this research is using purposive sampling technique in order to obtain 244 research sample data. The analysis carried out in this study used Microsoft Excel 2016 and hypothesis testing using Panel Data Regression Analysis with the Eviews version 12 application and a significance level of 5%. The results of the study partially show that, (1) Capital Structure has no effect on Firm Value, (2) Liquidity has no effect on Firm Value, and (3) Profitability has no effect on Firm Value.